2017
DOI: 10.1021/acs.inorgchem.7b01945
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Nitro vs Nitrito Coordination in Cytochrome c′ Using Vibrational Spectroscopy and Density Functional Theory

Abstract: Nitrite coordination to heme cofactors is a key step in the anaerobic production of the signaling molecule nitric oxide (NO). An ambidentate ligand, nitrite has the potential to coordinate via the N- (nitro) or O- (nitrito) atoms in a manner that can direct its reactivity. Distinguishing nitro vs nitrito coordination, along with the influence of the surrounding protein, is therefore of particular interest. In this study, we probed Fe(III) heme-nitrite coordination in Alcaligenes xylosoxidans cytochrome c′ (AXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 59 publications
(139 reference statements)
1
21
0
Order By: Relevance
“…from lysine or histidine providing further evidence of nitrito-coordination. This interpretation is broadly in accordance with a resonance Raman study of the nitrite bound form of WT HHMb at ambient temperature which only identified a high-spin nitrito-bound species [ 38 ], with no evidence of resonances associated with the nitro-species characterised in a variant of cytochrome c ′ [ 39 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…from lysine or histidine providing further evidence of nitrito-coordination. This interpretation is broadly in accordance with a resonance Raman study of the nitrite bound form of WT HHMb at ambient temperature which only identified a high-spin nitrito-bound species [ 38 ], with no evidence of resonances associated with the nitro-species characterised in a variant of cytochrome c ′ [ 39 ].…”
Section: Discussionsupporting
confidence: 85%
“…The asymmetry of the g ≈ 3.0 feature in our samples is indicative of some degree of heterogeneity, possibly due to the presence of both cis and trans linkage isomers of the nitrito-bound species [ 39 ]. This is accounted for in our simulation of the experimental data ( Figure 3B ) by including more than one low-spin species and together these represent ≈98% of the heme iron the remaining 2% being accounted for by the high-spin nitrito-species.…”
Section: Discussionmentioning
confidence: 99%
“…Support for low-energy differences between the N -nitro and O -nitrito binding modes in heme proteins and their truncated active site models comes from density functional theory (DFT) calculations that predict the N -nitro mode to be lower in energy by a few kilocalories per mole. ,, A recent detailed quantum chemical analysis of electron paramagnetic resonance spectral data for Mb III –nitrite, however, supports the O -nitrito mode of binding to the metal center as observed experimentally. These results suggest that the Mb (and Hb) distal pocket environments with the single His64 H-bonding residue in these proteins are somewhat unique in their interactions with nitrite.…”
mentioning
confidence: 99%
“…The N -nitro binding mode remains the most common mode of binding of nitrite to heme Fe centers, despite the differences in proximal ligation to heme (e.g., His for cyt cd 1 NiR, Cys for SiR, and Lys for cyt c NiR), macrocycle saturation (e.g., d vs c heme), and distal pocket amino acid identities. The first suggestions of a possible O -nitrito mode of binding to a heme protein was that for ferric human hemoglobin Hb III –ONO described by Hartridge in 1920 and Barnard in 1937, although this binding mode was not structurally confirmed until almost a century later with our reports on the structures of the nitrite adducts of horse heart (hh) Mb III and its derivatives and ferric Hb III . , …”
mentioning
confidence: 99%
“…Moreover, though the NO 2 group is having electron-withdrawing nature, it can coordinate with metal centers through lone pair electrons of N or O atoms. [81,82] Due to the coordination tendency of -NO 2 group with the metal center, it can coordinate with defects of ZnO and satisfy the O vacancies. The increasing order of passivation tendency can be followed as: NO 2 < COOH < OH.…”
Section: Surface Passivation Studies and Charge Transfer Mechanismmentioning
confidence: 99%